2022
DOI: 10.1002/saj2.20363
|View full text |Cite
|
Sign up to set email alerts
|

Effects of arbuscular mycorrhizal fungi on improvement of degraded landscape soil in an ionized rare earth mining area, subtropical China

Abstract: The disordered mining of ion‐type rare soil has caused significant ecological and environmental problems. Arbuscular mycorrhizal fungi (AMF) can promote soil quality, providing new ideas about the ecological restoration of degraded soil. In this study, the degraded ion‐type rare earth tailing soils in Xinfeng County, southern Jiangxi Province, was used as a research object. The soil was subjected to different restoration methods (biochar + fly ash + surface vegetation planting) for 2 yr. A total of six treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 53 publications
0
1
0
Order By: Relevance
“…Claroideoglomus claroideum contributed to the increase in AS, mainly in the Typic Distrustert. It has been established that the genus Claroideoglomus, as well as other AMF, can improve soil structure and increase the stability of aggregates, mainly of the macroaggregate type (>0.25 mm) [75,76]. This is the opposite of what happened with the AMF consortium, which was less effective than that of the individual AMF.…”
Section: Aggregates Stabilitymentioning
confidence: 99%
“…Claroideoglomus claroideum contributed to the increase in AS, mainly in the Typic Distrustert. It has been established that the genus Claroideoglomus, as well as other AMF, can improve soil structure and increase the stability of aggregates, mainly of the macroaggregate type (>0.25 mm) [75,76]. This is the opposite of what happened with the AMF consortium, which was less effective than that of the individual AMF.…”
Section: Aggregates Stabilitymentioning
confidence: 99%
“…Nicolson, which are synonymous and fall under the genus Glomus [22], have been widely used to promote plant growth [23,24]. Preliminary studies indicated that S. viscosum application could enhance phosphorus levels in the phosphorusdeficient soils of China's subtropical climate zone [25], where natural T. ciliata var. pubescens forests were found, implying potential growth benefits for T. ciliata var.…”
Section: Introductionmentioning
confidence: 99%